Hedonic regression model : influence of housing characteristics and housing lease on HDB's resale price - Ng, Darren Kaiwen (Nanyang Technological University, 2021)
Singapore is encountering an unprecedented situation of public housing flat lease decay. Some 665,000 public housing flats, or 62% of all public housing flats built by Housing Development Board (HDB) will be above aged 35 by 2025. In other words, these public housing flats have less than 65 years before the maturity of their lease. Yet, existing literature has been centred on the marginal effect of locational, neighbourhood, and structural variables to explain the HDB resale property prices. To fill the above literature gap, this paper aims to introduce housing lease years expired as a contractual variable and utilize a robust hedonic regression model to analyse housing lease relationship and its marginal contribution to resale HDB prices. The result shows that the contractual variable, in number of years lease expired, is a statistically significant variable and effects a decline in resale HDB prices. Moreover, additional analysis suggest that the effect of lease decay may even accelerate for older resale HDB flats.